2002
DOI: 10.1029/2001wr000989
|View full text |Cite
|
Sign up to set email alerts
|

Energy partitioning between latent and sensible heat flux during the warm season at FLUXNET sites

Abstract: [1] The warm season (mid-June through late August) partitioning between sensible (H ) and latent (LE ) heat flux, or the Bowen ratio (b = H/LE ), was investigated at 27 sites over 66 site years within the international network of eddy covariance sites (FLUXNET). Variability in b across ecosystems and climates was analyzed by quantifying general climatic and surface characteristics that control flux partitioning. The climatic control on b was quantified using the climatological resistance (R i ), which is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
193
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(210 citation statements)
references
References 61 publications
16
193
0
1
Order By: Relevance
“…This was similar to a broadleaved temperate deciduous forest in North America, where a study showed thatř anged from 0Ð68 to 0Ð78 over three observation years (Wilson and Baldocchi, 2000). However, theˇvalue at the mixed broadleaved-pine forest was generally high compared with those in other temperate deciduous forests, and even higher than most temperate coniferous forests, which typically had a highˇvalue (Wilson et al, 2002b). For example, the mean annualˇfor a temperate deciduous forest in south-central Indiana, USA, was 0Ð59 (Oliphant et al, 2004).…”
Section: Bowen Ratiosupporting
confidence: 63%
“…This was similar to a broadleaved temperate deciduous forest in North America, where a study showed thatř anged from 0Ð68 to 0Ð78 over three observation years (Wilson and Baldocchi, 2000). However, theˇvalue at the mixed broadleaved-pine forest was generally high compared with those in other temperate deciduous forests, and even higher than most temperate coniferous forests, which typically had a highˇvalue (Wilson et al, 2002b). For example, the mean annualˇfor a temperate deciduous forest in south-central Indiana, USA, was 0Ð59 (Oliphant et al, 2004).…”
Section: Bowen Ratiosupporting
confidence: 63%
“…Law et al, 2002;Hibbard et al, 2005;Reichstein et al, 2007b;Yuan et al, 2007) and ecosystem responses to climate anomalies and interannual variability (e.g. Wilson et al, 2002;Ciais et al, 2005;Reichstein et al, 2007a), or conducting inverse modeling studies to constrain carbon fluxes (e.g. Gerbig et al, 2003;Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In general, during the daylight hours, aerodynamic and canopy resistances are much lower than those during the nights (Blondin 1991;Tsai et al 2007). Typical values of daytime aerodynamic and canopy resistances observed in various land covers in the summer can be found in Wilson et al (2002). Therefore, from the Fig.…”
Section: Optimal Effective Thicknessmentioning
confidence: 95%
“…In addition, qG 0 * /qT 0 * of the diurnal frequency component is also shown in the figure. At the site, the daytime aerodynamic and canopy resistances in the summer are about 37 and 60 s m -1 , respectively (Wilson et al 2002). Following the method of Wilson et al (2002), r a is derived from the sum of the resistance to momentum transport and an excess resistance for scalar fluxes (Verma et al 1986) and r c is determined according to the PenmanMonteith approximation to the big leaf equations (Jarvis and McNaughton 1986;Shuttleworth et al 1984).…”
Section: Case Study-a Cropland Sitementioning
confidence: 99%
See 1 more Smart Citation